Legal Connections for the Settlement of Criminal Cases for TNI Soldiers According to Aceh Qanun Number 7 of 2013 with Military Law - Wahyudi, Misran; Munajat, Makhrus; Ocktoberrinsyah, Ocktoberrinsyah (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: The enactment of Aceh Qanun No. 7 of 2013 on the Law of Jinayat Procedural creates a separate problem for the criminal law enforcement system for TNI soldiers in Aceh. Reason, because the settlement of connectivity cases for TNI soldiers has previously been regulated in Law No. 31 of 1997 on Military Courts, however, Aceh Qanun No. 7 of 2013 also regulates the same thing, but with a different legal substance. The dualism of this arrangement can lead to clashes, Aceh Qanun vis a vis military law. This article analyzes how the law applies to the qanun in resolving connectivity cases for TNI soldiers in Aceh? and how is the law enforcement system? These problems were analyzed objectively using the theory of legal validity, and the theory of law enforcement. The method used is doctrinal research which focuses on the results of the study of various secondary data, supported by primary data in the form of interviews with resource persons, and uses a statutory approach and a conceptual approach. The findings of the research, namely: First, Aceh Qanun Number 7 of 2013 does not apply binding for every TNI soldier who performs jarimah together with those who are subject to the Aceh Islamic Sharia judiciary. Second, law enforcement on connectivity cases involving TNI soldiers is resolved through a splitsing mechanism, namely that the perpetrators of the finger who are members of the TNI are resolved through military courts, while the perpetrators of the crime who are civilians are resolved through the Islamic Sharia courts in Aceh.Abstrak: Berlakunya Qanun Aceh Nomor 7 Tahun 2013 tentang Hukum Acara Jinayat menjadi problematika tersendiri dalam penegakan hukum pidana bagi prajurit TNI di Aceh. Penyelesaian perkara koneksitas bagi prajurit TNI sebelumnya telah diatur dalam Undang-Undang Nomor 31 Tahun 1997 tentang Peradilan Militer, namun Qanun Aceh Nomor 7 Tahun 2013 juga turut mengatur hal yang sama, tetapi dengan substansi hukum yang berbeda. Dualisme pengaturan ini dapat menimbulkan benturan, Qanun Aceh vis a vis hukum militer. Artikel ini menganalisis bagaimanakah keberlakuan hukum qanun tersebut dalam penyelasaian perkara koneksitas bagi prajurit TNI di Aceh dan juga bagaimana pula sistem penegakan hukumnya. Persoalan tersebut dikaji dengan menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Adapun analisisnya dilakukan dengan menggunakan teori validitas hukum dan teori penegakan hukum. Metode yang digunakan adalah doctrinal reaserch yang menitikberatkan hasil telaah berbagai data sekunder, dengan didukung data primer berupa wawancara dengan narasumber. Dari kajian dan analisis yang telah dilakukan diperoleh simpulan bahwa: Pertama, Qanun Aceh Nomor 7 Tahun 2013 tidak berlaku mengikat terhadap prajurit TNI yang terlibat perkara koneksitas di Aceh. Kedua, penegakan hukum terhadap perkara koneksitas yang melibatkan prajurit TNI diselesaikan melalui mekanisme splitsing, yakni pelaku jarimah yang merupakan anggota TNI diselesaikan melalui peradilan militer, sedangkan bagi orang sipil diselesaikan melalui peradilan Syariat Islam di Aceh.